Being mindful in the tax context in Italy: Examining whether and how mindfulness relates with tax evasion intentions and support for tax progressivity. - Valeria De Cristofaro (Public Library of Science (PLoS), 2021)
Two studies explored whether and how mindfulness relates with citizens' tax evasion intentions and support for progressive tax rates. Based on theoretical and empirical grounds, in Study 1 (N = 1,175) we proposed that mindfulness would be negatively related with tax evasion intentions through decreased social dominance orientation. Drawing on Duckitt's dual-process motivational model, in Study 2 (N = 722) we proposed that mindfulness would be positively related with support for progressive taxation through the mediation of lower competitive-jungle beliefs, and then lower social dominance orientation. Instead, we did not expect to find mediation of the link between mindfulness and support for progressive taxation through dangerous-world beliefs and right-wing authoritarianism. These studies inform about the motivational pathways through which mindfulness relates with tax evasion intentions and support for progressive taxation.